2013
DOI: 10.5209/rev_psic.2013.v9.n2-3.40902
|View full text |Cite
|
Sign up to set email alerts
|

Detección de duelo complicado

Abstract: ResumenObjetivo: Conocer en profundidad el fenómeno del duelo complicado o patológico, y recabar aquellos indicadores de detección y evaluación que nos permitan su pronta identificación en la práctica clínica.Método: Tras una amplia revisión de la literatura científica aparecida en los últimos años, y a la luz de nuestra experiencia profesional, se realizó una recopilación de los indicadores más significativos.Resultados: Presentamos los principales criterios diagnósticos e instrumentos de medida utilizados en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
37

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 43 publications
0
39
0
37
Order By: Relevance
“…It is also important to identify those factors that may protect people who are going to experience a grief process. The efficient and effective clinical intervention has always considered important both the recovery and the promotion of the individual's resources and attention to their deficits (Barreto et al, 2008). However, there is little information from which we can draw definite conclusions.…”
Section: Predictors In Complicated Grief: a Risk Factor Overviewmentioning
confidence: 90%
See 4 more Smart Citations
“…It is also important to identify those factors that may protect people who are going to experience a grief process. The efficient and effective clinical intervention has always considered important both the recovery and the promotion of the individual's resources and attention to their deficits (Barreto et al, 2008). However, there is little information from which we can draw definite conclusions.…”
Section: Predictors In Complicated Grief: a Risk Factor Overviewmentioning
confidence: 90%
“…Complicated grief interferes significantly in the overall functioning of people, compromising their health and as stated by Maddocks (2003), it may last for years or even become chronic (Barreto et al, 2008) It is difficult to estimate the incidence of complicated grief in the general population. Different authors are interested in this problem and have observed that after the loss of a significant person, speaking of estimated averages, in the general population, two thirds of mourners evolve normally and the rest suffer alterations in their physical health, mental health or both (Olmeda, García Olmos & Basurte, 2002).…”
Section: Complicated Grief: a Brief History Of The Evolution Of The Cmentioning
confidence: 99%
See 3 more Smart Citations